REHUMANIZING RESISTANCE: HUMAN METAPHORS IN MAHMOUD DARWISH’S SYAJARAH AL-ZAITŪN AL-SĀNIYAH FROM A COGNITIVE SEMANTIC PERSPECTIVE - Arilla, Kisti (Hijai - Journal on Arabic Language and Literature, 2026)
This study identifies and analyzes human metaphors in Mahmoud Darwish’s poem Syajarah al-Zaitūn al-Sāniyah through the cognitive semantic framework of Michael C. Haley. Human metaphors, which constitute the highest tier in Haley’s nine-level metaphorical hierarchy, involve the mapping of psychological, social, and moral human attributes onto non-human entities. Seven metaphorical expressions are identified and analyzed thematically, revealing how the olive tree is systematically constructed as an entity possessing emotional transcendence, social authority, existential paradox, communicative ethics, and moral agency. This study argues that Darwish employs human metaphors not merely as aesthetic devices but as a cognitive strategy of rehumanization: a deliberate reclamation of full humanity for a people subjected to colonial dehumanization. The olive tree functions simultaneously as a symbol of steadfastness, dignified resistance, and historical legitimacy deeply rooted in Palestinian culture and collective memory. By demonstrating how metaphorical language encodes socio-political realities, this study contributes to the growing field of cognitive literary studies, particularly in the context of Arabic poetry and resistance literature.